ChemInform Abstract: Copper‐Catalyzed Selective Syntheses of Markovnikov‐Type Hydrothiolation Products and Thioacetals by the Reactions of Thiols with Alkenes Bearing Heteroatoms. Issue 43 (7th October 2016) - Xi, Hui; Ma, Enlu; Li, Zhiping
Abstract: Both classes of title compounds are readily available by simply switching the copper catalyst.